Predictive Biomarkers in Oncology 2018
DOI: 10.1007/978-3-319-95228-4_12
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cell Signaling Pathways in Cancer

Abstract: There are many different signaling pathways that contribute to development and cellular homeostasis. In diseases, especially cancer, development components of these pathways often become mutated or overexpressed causing dysregulation of cellular signaling. This chapter provides an overview of the key pathways involved in tumor development and progression and studies some of the complications associated with therapeutic targeting, namely signaling cross talk and biomarker identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…We identified 12 important pathways that might have an essential role in the incidence and development of LUAD: pathways in cancer, ubiquitin-mediated proteolysis, protein processing in the endoplasmic reticulum, necroptosis, hypertrophic cardiomyopathy, cardiac muscle contraction, focal adhesion, the PI3K–Akt and Ras signaling pathways, the neurotrophin and mTOR signaling pathways, and the MAPK signaling pathway. Many studies have reported that the PI3K–Akt signaling pathway, the Ras signaling pathway, the neurotrophic-signaling pathway, the mTOR-signaling pathway, and the MAPK signaling pathway are regulated in the development of lung adenocarcinoma patients [ 58 , 59 ]. The PI3K/AKT/mTOR signal pathway is a key intracellular signal transduction pathway, with an essential function in cell proliferation, growth, survival, vesicle trafficking, glucose transport, and cytoskeletal organization.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 12 important pathways that might have an essential role in the incidence and development of LUAD: pathways in cancer, ubiquitin-mediated proteolysis, protein processing in the endoplasmic reticulum, necroptosis, hypertrophic cardiomyopathy, cardiac muscle contraction, focal adhesion, the PI3K–Akt and Ras signaling pathways, the neurotrophin and mTOR signaling pathways, and the MAPK signaling pathway. Many studies have reported that the PI3K–Akt signaling pathway, the Ras signaling pathway, the neurotrophic-signaling pathway, the mTOR-signaling pathway, and the MAPK signaling pathway are regulated in the development of lung adenocarcinoma patients [ 58 , 59 ]. The PI3K/AKT/mTOR signal pathway is a key intracellular signal transduction pathway, with an essential function in cell proliferation, growth, survival, vesicle trafficking, glucose transport, and cytoskeletal organization.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of tumor processes, special attention is paid to signaling pathways that are responsible for the aberrant cell growth, survival, genome maintenance, etc. [ 155 ]. Signalome study provides another level for deciphering pathological processes and uses it to inform new treatments for precision medicine in cancer [ 156 ].…”
Section: Comparison Of Hepg2 Normal Hepatocyte Hb and Hccmentioning
confidence: 99%
“…Hypoxia-inducible factor signalling pathway (HIF-signalling) is described for different tissues such as brain 1 , 2 , lungs 3 , 4 , cardio-vascular system 5 , 6 , muscles 7 9 or skin 10 14 . In the given tissues, HIF-signalling has a different priority compared to the rest of the affected growth, metabolic and transcription pathways 15 – 18 . In the case of malignant melanoma (MM) the HIF-signalling pathway is one of the most dominant pathways 11 , 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%